The Effect of Punica granatum Leaf Tea on Potassium Oxonate Induced Gout in Male Wistar Rats - Akinniyi Ezekiel Wonderful; Umaru Hauwa Aduwamai (African Journal of Biochemistry and Molecular Biology Research, 2026)
Gout is a prevalent and debilitating inflammatory condition caused by the deposition of monosodium urate crystals in the joints, leading to acute pain, swelling, and redness. This study aimed to evaluate the effect of Punica granatum leaf tea on potassium oxonate-induced gout in male Wistar rats. Thirty rats were allocated into six groups of five animals each, and gout was induced by intraperitoneal administration of potassium oxonate at 250 mg/kg body weight for 14 days. P. granatum leaf tea was administered at doses of 10, 20, and 30 mg/kg body weight. The findings showed that potassium oxonate significantly increased serum uric acid, creatinine, IL-1β, IL-6, TNF-α, and hepatic xanthine oxidase activity relative to the normal control. Among the tested doses, 30 mg/kg body weight produced a significant (p < 0.05) reduction in uric acid (4.80 ± 0.06 mg/dL vs. 7.37 ± 0.15 mg/dL), IL-1β (25.41 ± 0.79 pg/mL vs. 31.45 ± 2.71 pg/mL), and hepatic xanthine oxidase activity (5.93 ± 0.20 U/L vs. 11.89 ± 1.11 U/L), with effects comparable to the standard drug group. The same dose also showed a more pronounced effect than the standard drug in reducing TNF-α (7.44 ± 0.58 pg/mL vs. 10.95 ± 1.87 pg/mL) and ALP (63.16 ± 2.06 U/L vs. 68.00 ± 1.98 U/L). The study concludes that Punica granatum leaf tea exhibits anti-hyperuricemic, anti-inflammatory, and organ-protective effects in potassium oxonate-induced gout, highlighting its potential contribution as a natural therapeutic candidate for gout management.